2009
DOI: 10.1016/j.bbagrm.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and Sp3 regulate transcription of the cyclin-dependent kinase 5 regulatory subunit 2 (p39) promoter in neuronal cells

Abstract: Cyclin dependent kinase 5 (cdk5) activity is critical for development and function of the nervous system. Cdk5 activity is dependent on association with the regulators p35 and p39 whose expression is highly regulated in the developing nervous system. We have identified a small 200bp fragment of the p39 promoter that is sufficient for cell type-specific expression in neuronal cells. Mutational analysis revealed that a cluster of predicted binding sites for Sp1, AP-1/CREB/ATF and E box-binding transcription fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…4). Furthermore, earlier reports by Valin et al, showed the importance of repeated GC box elements that bind Sp1, Sp3 and Sp4 in-vitro , to direct neuron-specific expression of the cdk5 regulator p35 (Valin et al, 2009). Thus, these posttranslational regulators of tau may also be subject to the same epigenetic reprogramming and transcriptional machinery that also impacts tau gene expression, culminating in not only an elevation of total tau but also in the enzymes involved in its phosphorylation (Bihaqi et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…4). Furthermore, earlier reports by Valin et al, showed the importance of repeated GC box elements that bind Sp1, Sp3 and Sp4 in-vitro , to direct neuron-specific expression of the cdk5 regulator p35 (Valin et al, 2009). Thus, these posttranslational regulators of tau may also be subject to the same epigenetic reprogramming and transcriptional machinery that also impacts tau gene expression, culminating in not only an elevation of total tau but also in the enzymes involved in its phosphorylation (Bihaqi et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Cdk5/p39 is also responsible for Munc18-1 phosphorylation during Ca ++ -induced insulin exocytosis [31] and phosphorylates the microtubule protein tau in the developing mouse brain [31]. The in vivo specificity of Cdk5/p39 versus Cdk5/p35 may be controlled by spatial and temporal regulation of their expression [32, 33] or by specific subcellular localization mediated by particular binding partners of p35 and p39 [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The in silico prediction analysis showed that FTO‐ risk variants could have a direct effect on modulating binding sites of transcription factors such as SP1 , SP2 and FOXP1 during brain development, which suggests a possible effect of these transcription factors on a FTO ‐risk variant dependent on brain development mechanism. Supporting these data, in animal models it has been described that alterations in expression levels of these transcription factors ( SP1 , SP2 and FOXP1 ) have a direct effect reducing the morphogenesis of the brain (Li et al., ; Valin, Cook, Ross, Saklad, & Gill, ). Binding sites of SP1 and SP2 were predicted to be disturbed by BD‐associated variants, and are transcription factors that play critical roles in embryonic and early development (Safe, Imanirad, Sreevalsan, Nair, & Jutooru, ).…”
Section: Discussionmentioning
confidence: 83%